Globally increased cropland soil exposure to climate extremes in recent decades - Luwei Feng; Yumiao Wang; Rasmus Fensholt; Xiaoye Tong; Torbern Tagesson; Xiaoxin Zhang; Jonas Ardö; Jie Zhou; Wenxuan Shao; Yujie Dou; Yirong Sang; Feng Tian (Nature Communications)
Abstract Soil quality is fundamental to nutrient-rich food production and the sustainability of terrestrial ecosystems. However, inappropriate agricultural practices often lead to persistent soil exposure to air and sunlight, which increases soil organic matter losses and erosion risks, particularly under climate extremes. Here, we provide a satellite-based mapping of daily soil exposure occurrence across global croplands from 2001 to 2022 and evaluate the associated degradation risks caused by extreme climate events. We find that while 57% of global croplands experienced a reduction in soil exposure duration in the past two decades, 86% are increasingly subjected to climate extremes. The areas exposed to increasing climate extremes tend to have higher soil organic carbon levels, indicating an intensified degradation risk of global nutrient-rich cropland soils. Our study offers spatio-temporally explicit insights into global cropland soil exposure and its vulnerability to climate extremes, providing evidence to support improvements in sustainable agriculture practices.